La realtà dei genitori separati e il supporto emotivo e relazionale nella separazione: il movimento dei GENitori sinGLE (GenGle) come gruppo di mutuo-auto-aiuto online. Uno sguardo pedagogico-sociale - Mancaniello, Maria Rita (Rivista Italiana di Educazione Familiare, 2019)
Self-help is considered a culture, a social movement, a lifestyle based on reciprocity, and a methodology to overcome situations of hardship. It is based on the participatory action of people within a group who, starting from a problem, decide to activate themselves to provide help contributing with their own history and their own knowledge, and skills. The focus of Self-Mutual-Aid (SMA) is the group; this experience makes subjects feel united. Emotional participation in group life triggers a circular communication, which lead members to recognize and experience skills, even identifying unexpressed personal characteristics. The diffusion of communication technologies has enabled the development of brand new forms of self-help. The potential offered by Web 2.0 contributed to redefine the configuration of SMA. The phenomenon of online SMA groups is growing, taking on different forms, such as: SMH online groups, SMA communities, episodic experiences. Online SMA groups represent an important source of support, and this due to the potential that the network has in helping relationships. The analysis is focused on a particular virtual platform, called GenGle, which is, to date, the first social network dedicated to single parents and their children. GenGle was born in 2014 as a social aggregator; it was created to provide real support to single-parent families. The fundamental aim of this research is to evaluate the potential of GenGle movement, as a group of Self-Mutual-Aid, and if and how it could be considered an effective model of educational care.